APPLICABILITY INVESTIGATION OF FAILURE CRITERION FOR POST-BUCKLING ANALYSIS OF STIFFENED COMPOSITE PANELS - LIN GuoWei; LI XinXiang (Jixie qiangdu)
In order to select the reasonable failure criterion of post-buckling analysis of stiffened composite panels,Lstiffener specimen with long post-buckling histories was designed and crippling test was conducted. FEA model with the consideration of progressive failure was established. Load-strain curve and buckling load and damage load were also presented. An excellent agreement is found between the analytical prediction and the experimental data. And the failure mode predicted is also consistent with the test results. The validity of analysis method is proved. Five different failure criterions are adopted respectively in the FEM analysis and damage loads as well as failure modes is obtained. The analysis results indicate that the validity of different failure criterion would be verified to avoid arbitrary selection of them by combination of L-stiffener specimen test and simulation. This work can provide reference to the post-buckling design and analysis of stiffened composite panels.